Why Women Buy During Live Shopping? A Qualitative Study on Consumer Experience in Makassar City - Muhammad Ilham Wardhana Haeruddin (Journal Management & Economics Review (JUMPER), 2026)
The phenomenon of live shopping has grown rapidly in Indonesia, especially among women as the dominant consumer group. This study aims to explore women's experiences in shopping through live shopping on digital platforms managed by Micro, Small, and Medium Enterprises (MSMEs) in Makassar City. Using a phenomenological qualitative approach, this study involved 12 informants, comprising MSME owners and employees who actively managed live shopping sessions. Data were collected through in-depth interviews, hands-on observation, and documentation studies. Data analysis was carried out using the Miles, Huberman, and Saldaña thematic analysis model, which included data condensation, data presentation, and drawing conclusions. The validity of the data is guaranteed through source triangulation and member checking. The results of the study revealed four main themes that drive women's purchasing decisions in live shopping, namely: (1) immersive interactive experiences create a sense of emotional involvement; (2) trust based on direct product demonstration; (3) psychological stress, time and stock limitations (fear of missing out / FOMO); and (4) community influence and social validation from fellow viewers. These findings contribute to the development of a theory of digital consumer behavior while providing practical implications for MSME marketing strategies in optimizing live shopping sessions oriented to the women's segment.